A study on the floating bridge type horizontal axis tidal current turbine for energy independent islands in Korea. (November 2017) - Kim, Seung-Jun; Singh, Patrick Mark; Hyun, Beom-Soo; Lee, Young-Ho; Choi, Young-Do
Abstract: The tidal currents in the region of South-Western sea of Korea can be utilized for the development of tidal current power, benefiting many fishing nurseries and nearby islands. Furthermore, it can contribute to promoting energy independent islands. This study focuses on floating-bridge type small tidal current turbine, which can be installed between the small islands limited space unlike large tidal current turbines. The aim is to develop a floating-bridge type 15 kW-class small horizontal axis tidal current turbine. As part of the research for the reduced model experiment of hydrofoils, a 50 W-class horizontal axis tidal current turbine model was investigated. Therefore, for this study, blade design was carried out using two different hydrofoils (MNU26 and NACA63421). Performance and hydrodynamic characteristics are investigated by using computational fluid dynamics and experimental methods. Among the two blades, NACA63421 blade showed the best power coefficient at low Reynolds number, whereas MNU26 blade performed better for higher Reynolds number. The MNU26 hydrofoil was applied to the blade design from the previous study. The MNU26 hydrofoil has a 26% thickness in contrast to the NACA63421, which has a 21% thickness. This indicates that the MNU26 can be applied throughout the blade length for the 15 kW-class turbine whilst providing good structural strength. Highlights: Floating-bridge type small (15 kW-class) tidal current turbine is suggested for energy independent islands. Two hydrofoils are investigated (MNU26 from previous study, NACA63421 from reference). 50 W model was investigated and compared by experiment and CFD methods. The design requirements were achieved for both hydrofoils.